Synthesis and applications of porous non-silica metal oxide submicrospheres - Boyjoo, Yash; Wang, Meiwen; Pareek, Vishnu; Liu, Jian; Jaroniec, M. (RSC Publishing, 2016)
© 2016 Royal Society of Chemistry. Nowadays the development of submicroscale products of specific size and morphology that feature a high surface area to volume ratio, well-developed and accessible porosity for adsorbates and reactants, and are non-toxic, biocompatible, thermally stable and suitable as synergetic supports for precious metal catalysts is of great importance for many advanced applications. Complex porous non-silica metal oxide submicrospheres constitute an important class of materials that fulfill all these qualities and in addition, they are relatively easy to synthesize. This review presents a comprehensive appraisal of the methods used for the synthesis of a wide range of porous non-silica metal oxide particles of spherical morphology such as porous solid spheres, core-shell and yolk-shell particles as well as single-shell and multi-shell particles. In particular, hydrothermal and low temperature solution precipitation methods, which both include various structure developing strategies such as hard templating, soft templating, hydrolysis, or those taking advantage of Ostwald ripening and the Kirkendall effect, are reviewed. In addition, a critical assessment of the effects of different experimental parameters such as reaction time, reaction temperature, calcination, pH and the type of reactants and solvents on the structure of the final products is presented. Finally, the practical usefulness of complex porous non-silica metal oxide submicrospheres in sensing, catalysis, biomedical, environmental and energy-related applications is presented.